Low dose versus standard dose rituximab for the treatment of antiphospholipid syndrome: A pilot study from a tertiary medical center - Gan, Yuzhou; Zhong, Xue; Zhao, Yawei; Li, Gongming; Ye, Hua; Li, Chun (Frontiers in Immunology, 2022)
Background: To investigate the therapeutic effects and safety of low-dose and standard-dose rituximab (RTX) in the treatment of antiphospholipid syndrome (APS). Methods: In this real-world study, we included 22 consecutive patients with APS who received RTX. Standard dose (SD) was defined as an overall dosage of RTX ≥ 1000mg in the induction period, and low dose (LD) was defined as an overall dosage of RTX <1000mg. Results: Of included patients, 1 patients died, 2 patients withdrew and 19 patients completed 6 months follow-up. Nine patients received SD-RTX and 13 patients received LD-RTX, and elder patients (LD-RTX vs. SD-RTX: 49.1 ± 15.5 vs. 35.8 ± 12.3, p = 0.044) and patients with later-onset (LD-RTX vs. SD-RTX: 46.8 ± 16.3 vs. 31.3 ± 13.6, p = 0.029) were more frequently included in LD-RTX than SD-RTX. Following 6 month RTX treatment, 8 patients (42.1%) achieved complete remission, 8 patients (42.1%) achieved partial remission and 3 patients (15.8%) showed no remission. The titers of anticardiolipin antibodies (baseline vs. 6 month: 30.8 (10.7, 90) vs. 19.5 (2.45, 69.10), p =0.023) and the levels of erythrocyte sedimentation rate (baseline vs. 6 month: 29 (6, 63.75) vs. 14 (8.5, 22.75), p =0.021) exhibited a significantly decrease in all APS patients. Remission rate and titers of anti-β2-glycoprotein I and lupus anticoagulant antiphospholipid antibodies did not differ significantly between two groups. Conclusion: RTX might be a safe and effective option for patients with APS, and low dose confers equal efficacy as standard dose. Further cohort studies are needed to confirm our findings.